Projeto Memória e Envelhecimento: capacitando profissionais e aprimorando aspectos cognitivos em idosos institucionalizados - Soares, Edvaldo [UNESP]; Oliveira, Tamara Pereira de [UNESP]; Komatsu, Patrícia Sayuri [UNESP]; Demartini, Stella Maira [UNESP]; Suziki, Michele Mita [UNESP]; Rodrigues, Mirela Mendes [UNESP]; Reis, Érica Gonçalves dos [UNESP]; Horimoto, Alessandra Tiemi [UNESP] (UPF Editora, 2010)
The increase in elderly population is a worldwide phenomenon and has different consequences not only in terms of health, but also in economic terms. One of those consequences is the institutionalization. The project, running in two elderly care institutions (hereafter IRLPi) located in Marília – SP aims to: a) Train multidisciplinary team to work in IRLPi’s; b) Develop and promote activities that improve life quality focusing on the preservation of mental health; c) study general and mental health conditions of patients under elderly care institution programs. The project was implemented in three phases: a) data collection and elaboration of plan of activities; b) Application of activities; and c) assessment/ analysis of results. Regarding Phase 1, data were collected from 3 forms, through which it was possible to verify: Institutional Data; Social Data and General Health. The data related to health were collected from the medication of continuous use. All data were launched into the database (Access) and subjected to the descriptive statistical analysis. Data related to mental health were confirmed from the application of clinical trials (Geriatric Depression Scale - EGD, and MMSE-T).

O aumento da população idosa é um fenômeno mundial e traz consequências diversas, não só em termos de saúde, mas também em termos econômicos. Uma dessas consequências é a institucionalização. O projeto, em execução em duas instituições residenciais de longa permanência para idosos (IRLPi) localizadas na cidade de Marília - SP, tem como objetivos: a) capacitar equipe multidisciplinar para atuar em IRLPi’s; b) elaborar e promover atividades que melhorem a qualidade de vida, com enfoque especial na preservação da saúde mental; c) estudar as condições de saúde geral e mental dos idosos institucionalizados. O projeto foi implantado em três fases: 1 - coleta de dados e elaboração de plano de atividades; 2 - aplicação de atividades; 3 - avaliação/análise de resultados. Em relação à fase 1, os dados foram colhidos por meio de três formulários, mediante os quais se verificaram dados institucionais, dados sociais e saúde geral. Os dados referentes à saúde foram colhidos a partir da medicação de uso contínuo. Todos os dados foram lançados em banco de dados (Access) e submetidos à análise estatística descritiva. Dados referentes à saúde mental foram confirmados pela aplicação de testes clínicos da escala geriátrica de depressão e do Mini-Exame do Estado Mental (GDE e MMSE-T nas siglas em inglês).
Project Memory and Aging: training professionals and improving cognitive aspects in patients under elderly care institution programs
Keywords: Institucionalização; Cognição; Cuidadores; Envelhecimento Humano; Plasticidade; Epidemiologia